Drug Repurposing of Pantoprazole and Vitamin C Targeting Tumor Microenvironment Conditions Improves Anticancer Effect in Metastatic Castration-Resistant Prostate Cancer - Li, Zhoulei; He, Peng; Long, Yali; Yuan, Gang; Shen, Wanqing; Chen, Zhifeng; Zhang, Bing; Wang, Yue; Yue, Dianchao; Seidl, Christof; Zhang, Xiangsong (Frontiers in Oncology, 2021)
The effective and economical therapeutic strategy for metastatic castration-resistant prostate cancer (mCRPC) is still requested from patients, who are not available for Lu-177 or Ra-223 treatment. Drug repurposing as a cost-effective and time-saving alternative to traditional drug development has been increasingly discussed. Proton pump inhibitors (PPIs) such as pantroprazole, which are commonly used as antacids, have also been shown to be effective in cancer chemoprevention via induction of apoptosis in multiple cancer cell lines. Vitamin C is an essential micronutrient for human body, has been proposed as a potential anti-cancer agent. In this context, have we investigated the combination of vitamin C and pantoprazole for the management of metastatic castration-resistant prostate cancer (mCRPC). Six chosen human adenocarcinoma cell lines were used to investigate the influence of pantoprazole on the microenvironment of cancer cells (extracellular pH and production of exosomes). Tumor growth and tumor 18F-FDG uptake in PC3 xenografts were analyzed following varied treatment. Our in vitro Results have suggested that pantoprazole enhanced the cytotoxic activity of vitamin C by regulating pH values and production of exosomes in cancer cells. Moreover, the synergistic effect of pantoprazole and vitamin C was pH-dependent since pantoprazole was more effective at a slightly acidic pH. In vivo, the combined treatment using pantoprazole and vitamin C produced better therapeutic outcomes than treatment with vitamin C or pantoprazole alone, as demonstrated via tumor growth and uptake of 18F-FDG. Therefore, we suggest that pantoprazole combined with vitamin C could be as a possible strategy to manage mCRPC.